The Minimum Inhibitory Concentration (MIC) And Minimum Bactericidal Concentration (MBC) Of Sambiloto Leaf Extract Against Enterococcus Faecalis - Ananda, Nihal Dea; Soebagio; Yogiartono, R. Mohammad.; Rachmadi, Priyawan (International Journal of Psychosocial Rehabilitation, 2020)
Background: Enterococcus faecalis is a bacteria that causes the failure of the root canal treatment. Sodium hypochlorite is often used as irrigation, but it caused irritate the tissue. The chemical compounds in sambiloto leaf are tannin, saponin, alkaloid, flavonoid, and andrographolide which have antibacterial potency. Purpose: To determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of sambiloto leaf extract against Enterococcus faecalis. Methods: Sambiloto leaf extract was made up to 5 concentrations which are 1,56%, 2,09%, 2,61% and 3,125%. 5 tubes consist of BHIB and 0,1 ml suspension of bacteria, 1 tube consist only with BHIB. 5 tubes added with sambiloto leaf extract in variated concentrations. The tube was incubated in an anaerobic jar at 37o C for 24 hours. Then the suspension of bacteria was subcultured in nutrient agar. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) counted manually. Results: Sambiloto leaf extract at a concentration of 1,56% showed inhibition of bacterial growth while the concentrations of 2,09% showed no bacterial growth. Conclusion: Sambiloto leaf extract has an antibacterial effect at a minimum inhibitory concentration of 1,56% and minimum bactericidal concentration of 2,09%